Influence of beneficial microorganisms on the agronomic behavior of potato crop cv. “Bicentenaria” - Flores, Pedro; Leon, Betsabe (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
The excessive use of chemical fertilizers causes alterations in soil microbial activity, environmental pollution and high production costs in potato cultivation (Solanum tuberosum L.). One way to avoid this effect is with the use of beneficial microorganisms, due to their ability to capture atmospheric nitrogen, produce growth-promoting substances such as indole acetic acid and solubilize inorganic phosphorus from insoluble compounds, which in turn time improves crop yields. The objective of this research was to evaluate the effect of the beneficial microorganisms as biofertilizers on growth and yield of potato crop. In a population of 1,600 potato plants cv. “Bicentenaria” four treatments were evaluated: Trichoderma harzianum (0.5 g.L-1), Glomus spp. (30 g.plant-1), efficient microorganisms (EM) (50 mL.L-1) and a control treatment (no application of microorganisms). A completely randomized experimental design with four repetitions per treatment was used. The effect of the treatments was evaluated using vegetative and reproductive variables. It was evident that the treatment with T. harzianum significantly favored the rest of the treatments in plant height at 90 days (43.60 cm), tuber weight (154 g) and yield (57.13 t.ha-1). The use of Glomus spp. and EM, had only a partial effect on the growth of the plants. The treatment with T. harzianum could represent an ecological agricultural alternative for potato production.